The price, efficacy, and safety of within-class targeted anticancer medicines between domestic and imported drugs in China: a comparative analysisResearch in context - Xingxian Luo; Xin Du; Lin Huang; Qixiang Guo; Ruijie Tan; Yue Zhou; Zhuangqi Li; Xuecai Xue; Taifeng Li; Kaidi Le; Feng Qian; Shein-Chung Chow; et al. (Elsevier, 2023)
Summary: Background: Affordability to novel anticancer drugs has become a major health issue in China. It is encouraging to note that China initiated its drug regulatory reform and national price negotiation policies since 2015. As a growing number of domestic within-class targeted anticancer drugs are approved in China, it is expected that this may reduce the price of novel anticancer drugs and improve the affordability of anticancer drugs. This study aimed to evaluate the price, efficacy, and safety of the within-class anticancer drugs between domestic and imported drugs approved in China from 2010 to 2022. Methods: The domestic and imported within-class targeted drugs for solid cancers approved in China between 2010 and 2022 were extracted. We classified it as a class of anticancer drugs based on the same indication and similar biological mechanism. The published literature derived from pivotal clinical trials of these domestic and imported drugs was identified based on the review report and the latest labels issued by the China National Medical Products Administration. We evaluated the monthly treatment price at launch and the latest (2022), primary efficacy endpoint and safety between domestic and imported anticancer drugs. Meta-analyses were further employed to evaluate the efficacy and safety of the domestic and imported anticancer drugs, including pooled hazard ratios (HR) for progression-free survival (PFS), overall survival (OS), objective response rates (ORR) for solid cancers, and relative risk for serious adverse events (SAE) and Grade ≥3 adverse events (AEs). Findings: In our cohort study, 12 within-class anticancer drugs with 7 cancer diseases were analyzed, including 18 domestic (21 indications; 21 pivotal trials) and 18 imported (21 indications; 27 pivotal trials) novel anticancer drugs, respectively. The median monthly treatment price of domestic and imported drugs from the years of launch to 2022 had significantly decreased by 71% and 62%, respectively. Moreover, the median monthly treatment price of domestic targeted anticancer drugs on the market at launch ($3786 vs. $5393, P = 0.007) and the latest ($1222 vs. $2077, P = 0.011) was significantly lower than that of imported drugs. No significant differences in median PFS gains (9.0 vs. 11.0 months; P = 0.24), OS gains (9.3 vs 10.6 months; P = 0.66), and ORR (57% vs 62%, P = 0.77) of targeted anticancer drugs in their pivotal trials were observed between the domestic and imported drugs. Additionally, there was no significant difference between domestic and imported drugs in the incidence of SAE (23% vs. 24%; P = 0.41) and Grade ≥3 AEs (59% vs. 57%; P = 0.45). These findings were also further confirmed in the meta-analyses for primary efficacy endpoints and safety outcomes. Interpretation: The prices of both domestic and imported anticancer drugs significantly decreased after market entry mainly due to the role of national price negotiations. The median monthly treatment price of domestic within-class targeted anticancer drugs was significantly lower than that of imported drugs. Furthermore, the efficacy and safety of domestic anticancer drugs were comparable to that of imported drugs. This evidence implicated that the development of within-class anticancer drugs with national price negotiations in China significantly improved the affordability for patients. Funding: This study was supported by postdoctoral fellowship from Tsinghua-Peking Joint Centers for Life Sciences (CLS).